Profile of Sexually Transmitted Diseases and The Influence of COVID-19 Pandemic on Sexual Transmitted Infection Testing in Dr. Moewardi General Hospital - Ellistasari, Endra Yustin; Mawardi, Prasetyadi; Primisawitri, Pratiwi Prasetya; Octarica , Stella Gracia (Indonesian Basic and Experimental Health Sciences, 2025)
Introduction Sexually transmitted infections (STIs) are diseases resulting from bacteria, viruses, or parasites transmitted during vaginal, anal, or oral sexual intercourse. The COVID-19 pandemic markedly influenced STI statistics, leading to potential underreporting of cases and heightened transmission rates. Objective : To analyse the profile of sexually transmitted infections and the influence of COVID-19 on STI assessments at the Dermatology and Venereology (DV) Outpatient Clinic of Dr. Moewardi General Hospital. Method A retrospective study using secondary data derived from medical records and registration logs at DV Outpatient Clinic of Dr. Moewardi General Hospital, spanning from January 2018 to December 2022.   Results 284 new STI cases were documented in the before pandemic lockdown period, however during the pandemic lockdown, there was a significant decline of 149 new cases. After the pandemic lockdown, there was 200 additional cases of STIs. Up to 90 patients with STIs were co-infected with HIV. The predominant instance of STIs was condyloma acuminata., and there was a strong correlation between gender and the incidence of STIs (p=0.000; p<0.05) Conclusion There was a sharp decline in STI cases during the COVID-19 pandemic and a surge in STI cases after the COVID-19 pandemic, predominantly featuring instances of condyloma acuminata and syphilis.